2011
DOI: 10.1186/1475-2875-10-210
|View full text |Cite
|
Sign up to set email alerts
|

Community screening and treatment of asymptomatic carriers of Plasmodium falciparum with artemether-lumefantrine to reduce malaria disease burden: a modelling and simulation analysis

Abstract: BackgroundAsymptomatic carriers of Plasmodium falciparum serve as a reservoir of parasites for malaria transmission. Identification and treatment of asymptomatic carriers within a region may reduce the parasite reservoir and influence malaria transmission in that area.MethodsUsing computer simulation, this analysis explored the impact of community screening campaigns (CSC) followed by systematic treatment of P. falciparum asymptomatic carriers (AC) with artemether-lumefantrine (AL) on disease transmission. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 24 publications
1
62
3
Order By: Relevance
“…Field and modeling studies suggest that PACD can reduce transmission when diagnostic tests detect most infections, with the longest period of reduction occurring in lower prevalence settings [21],[30],[31]. A recent study in Burkina Faso found no impact of PACD on parasite prevalence or incidence of clinical episodes after 12 months of follow up [32].…”
Section: Active Case Detection Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Field and modeling studies suggest that PACD can reduce transmission when diagnostic tests detect most infections, with the longest period of reduction occurring in lower prevalence settings [21],[30],[31]. A recent study in Burkina Faso found no impact of PACD on parasite prevalence or incidence of clinical episodes after 12 months of follow up [32].…”
Section: Active Case Detection Methodsmentioning
confidence: 99%
“…In such settings, campaigns should be conducted during the dry season, when mosquito densities are lowest and infections are most clustered, as this timing is likely to have the greatest impact on transmission [4],[21],[30].…”
Section: Considerations For Successful Acd Implementationmentioning
confidence: 99%
“…Several modeling attempts have demonstrated that targeting the asymptomatic parasite reservoir with MSaT or MDA could result in reductions in malaria transmission, even though some of the effects were modest [9,77,78]. Griffin et al found that absolute reductions of 5-12% in parasite prevalence could be achieved in low-to-moderate transmission settings (entomologic inoculation rates of 7-94 infective bites per person per year) with 80% coverage of annual single rounds of MSaT using RDTs, in conjunction with 80% ITN coverage over 15 years of sustained program; the addition of IRS would significantly improve the final outcome [9].…”
Section: What Theoretical Data Suggest That These Approaches Can Redumentioning
confidence: 99%
“…Incomplete coverage and imperfect diagnostics in MTAT campaigns result in a significant portion of the parasite reservoir being left untreated [1821]. This untreated reservoir will resume the cycle of transmission during the next rainy season.…”
Section: Resultsmentioning
confidence: 99%